2019
DOI: 10.15408/sjie.v8i2.11636
|View full text |Cite
|
Sign up to set email alerts
|

Political Dynasties and the Moderating Role of Good Public Governance

Abstract: The purpose of this study is to investigate the phenomena of political dynasties in Indonesia and its effect on local government performance. Moreover, this study also examines the moderating role of good public governance on the relationship between political dynasties and local government performance. Political dynasties define as the condition where local government head/vice head has a family connection with the head/vice head from the previous period or in other local government or with the legislative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Jika kepala daerah terpilih berdasarkan politik kekrabatan, maka hal ini dikhawatirkan dapat menimbulkan tindakan sewenang-wenang dan penyalahgunaan kekuasaan serta berpengaruh terhadap kinerja pemerintah daerah. 21 Politik Dinasti dalam pemilihan kepala daerah terhadap keberlangsungan demokrasi di Indonesia berpengaruh negatif terhadap kinerja pemerintah dan pelayanan publik. Praktik politik dinasti yang lazim diterapkan pada berbagai ini memang tidak dapat dihentikan, namun praktiknya dapat dikurangi secara masif.…”
Section: Pengaruh Politik Dinasti Dalam Pemilihan Kepala Daerah Terha...unclassified
“…Jika kepala daerah terpilih berdasarkan politik kekrabatan, maka hal ini dikhawatirkan dapat menimbulkan tindakan sewenang-wenang dan penyalahgunaan kekuasaan serta berpengaruh terhadap kinerja pemerintah daerah. 21 Politik Dinasti dalam pemilihan kepala daerah terhadap keberlangsungan demokrasi di Indonesia berpengaruh negatif terhadap kinerja pemerintah dan pelayanan publik. Praktik politik dinasti yang lazim diterapkan pada berbagai ini memang tidak dapat dihentikan, namun praktiknya dapat dikurangi secara masif.…”
Section: Pengaruh Politik Dinasti Dalam Pemilihan Kepala Daerah Terha...unclassified
“…Rusydi and Rossieta (2015) asserted that the implementation of the new public management is aimed to improve the efficiency and effectiveness of public services and its organizations. A strand of studies, Addink (2019); Lestiawan and Jatmiko (2016); Setyaningrum and Saragih (2019) suggested that application of the GPG will improve performance of public sector institutions. In addition, a study by examined the effect of GPG implementation on local government spending.…”
Section: Literature Review the Concept Of Good Public Governance (Gpg...mentioning
confidence: 99%
“…As the ruling party in Sragen Regency, PDIP can play a solid party machine to win the Pilkada contest. Although this is not a guarantee, because it was proven in the 2015 Sragen Pilkada, the candidate from this party suffered a defeat (Setiyoko, 2015�. Eighth, Sukoharjo Regency. The Large influence of kinship politics in the 2020 Sukoharjo Pilkada is in relative actor.…”
Section: B the Influence Of Political Kinship Actors In The 2020 Pilkada In Central Javamentioning
confidence: 99%